Per-operative findings in patients operated for spinal dysraphism: A study of 96 cases - Usman, Muhammad; Ali, Mumtaz; Khan, Khalid Mahmood; Siddique, Muhammad; Khanzada, Khalid; Ali, Azaz (Journal of Pediatric Neurology, 2011)
This study was conducted to study the perioperative findings in patients of spinal dysraphism. This observational study was conducted in Neurosurgery Department of Post Graduate Medical Institute, Lady Reading Hospital, Peshawar from January 2008 to December 2009. All the patients of spinal dysraphism less than 2 years of age were included in this study, while patients with ruptured spinal dysraphism at the time of presentation and with concomitant established hydrocephalus were excluded. Data was collected and analyzed by descriptive statistics using software SPSS version 17. Out of 96 patients operated for spinal dysraphism; 62 (64.58%) were males and 34 (35.42%) females. Eighty three patients (86.45%) were less than 1 yr, while 13 (13.54%) were above 1 yr. Peri-operative findings were: myelomeningocele in 50 (52.08%) patients, meningocele (MC) in 29 (30.20%), lipomyelomeningocele in six (6.25%), lipoma of cord with tethered cord in five (5.2%), MC with tethered cord in three (3.12%) patients, diastematomyelia in two (2.08%), while dermal sinus was found in one (1.04%) patient. In patients of spinal dysraphism less than 2 yr of age, more than 2/3rd of the patients presented with myelomeningocele and MC, while other features (such as lipomyelomeningocele, lipoma of cord with tethered cord, MC with tethered cord, diastematomyelia and dermal sinus) comprise only less than 20% of the spectrum.
Keywords: Spinal dysraphism; perioperative findings; myelomeningocele; meningocele